Nitrogen isotope fractionation explains the 15N enrichment of Antarctic cryptogams by volatilized ammonia from penguin and seal colonies - Bokhorst, Stef; van Logtestijn, Richard; Convey, Peter; Aerts, Rien (Polar Research, 2019)
Vegetation near bird and seal rookeries typically has high δ15N signatures and these high values are linked to the enriched δ15N values of rookery soils. However, Antarctic cryptogams are mostly dependent on atmospheric ammonia (NH3) and volatized NH3 from rookeries is severely depleted in δ15N-NH3. So there is an apparent discrepancy between the isotopically depleted source (NH3) and δ15N-enriched vegetation. In this article, we aim to resolve this discrepancy to better understand the mechanisms and processes involved in isotopic changes during nitrogen transfer between Antarctic marine and terrestrial ecosystems. Under laboratory conditions, we quantified whether volatized NH3 affects the isotopic signature of cryptogams. NH3 volatilizing from penguin guano and elephant seal dung was depleted (44–49‰) in δ15N when captured on acidified filters, compared to the source itself. Cryptogams exposed to the volatized NH3 were enriched (18.8–23.9‰) in δ15N. The moss Andreaea regularis gained more nitrogen (0.9%) than the lichen Usnea antarctica (0.4%) from volatilized NH3, indicating a potential difference in atmospheric NH3 acquisition that is consistent with existing field differences in nitrogen concentrations and δ15N between mosses and lichens in general. This study clarifies the δ15N enrichment of cryptogams resulting from one of the most important nitrogen pathways for Antarctic vegetation.
Keywords: Antarktis; fugler; kjemiske analyser; kryptogamer; lav; moser; planter; seler; økologi

Distribution, density and abundance of Antarctic ice seals off Queen Maud Land and the eastern Weddell Sea - Gurarie, Eliezer; Bengtson, John L; Bester, Marthán N; Blix, Arnoldus Schytte; Cameron, Michael; Bornemann, Horst; Nordøy, Erling S; Plötz, Joachim; Steinhage, Daniel; Boveng, Peter (Polar Biology, 2017)
Keywords: Sørishavet; Weddellhavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr; zoologi

The seasonal evolution of shelf water masses around Bouvetøya, a sub-Antarctic island in the mid-Atlantic sector of the Southern Ocean, determined from an instrumented southern elephant seal - Lowther, Andrew D.; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
Our study makes use of a fortuitous oceanographic data set collected around the remote sub-Antarctic island of Bouvetøya by a conductivity–temperature–depth recorder (CTD) integrated with a satellite-relayed data logger deployed on an adult female southern elephant seal (Mirounga leonina) to describe the seasonal evolution of the western shelf waters. The instrumented seal remained in waters over the shelf for 259 days, collecting an average of 2.6 (±0.06) CTD profiles per day, providing hydrographic data encompassing the late austral summer and the entire winter. These data document the thermal stratification of the upper water layer due to summer surface heating of the previous year's Antarctic Surface Water, giving way to a cold subsurface layer at about 100 m as the austral winter progressed, with a concomitant increase in salinity of the upper layer. Upper Circumpolar Deep Water was detected at a depth of approximately 200 m along the western shelf of Bouvetøya throughout the year. These oceanographic data represent the only seasonal time series for this region and the second such animal–instrument oceanographic time series in the sub-Antarctic domain of the Southern Ocean.
Keywords: AABW; Bouvetøya; biotelemetri; hydrografi; marin biologi; oseanografi; seler

Environmental influences on the at-sea behaviour of a major consumer, Mirounga leonina, in a rapidly changing environment - McIntyre, Trevor; Bornemann, Horst; de Bruyn, P J Nico; Reisinger, Ryan R; Steinhage, Daniel; Márquez, Maria E I; Bester, Marthán N; Plötz, Joachim (Polar Research, 2014)
Understanding the distribution and foraging ecology of major consumers within pelagic systems, specifically in relation to physical parameters, can be important for the management of bentho-pelagic systems undergoing rapid change associated with global climate change and other anthropogenic disturbances such as fishing (i.e., the Antarctic Peninsula and Scotia Sea). We tracked 11 adult male southern elephant seals (Mirounga leonina), during their five-month post-moult foraging migrations from King George Island (Isla 25 de Mayo), northern Antarctic Peninsula, using tags capable of recording and transmitting behavioural data and in situ temperature and salinity data. Seals foraged mostly within the Weddell–Scotia Confluence, while a few foraged along the western Antarctic Peninsula shelf of the Bellingshausen Sea. Mixed model outputs suggest that the at-sea behaviour of seals was associated with a number of environmental parameters, especially seafloor depth, sea-ice concentrations and the temperature structure of the water column. Seals increased dive bottom times and travelled at slower speeds in shallower areas and areas with increased sea-ice concentrations. Changes in dive depth and durations, as well as relative amount of time spent during the bottom phases of dives, were observed in relation to differences in overall temperature gradient, likely as a response to vertical changes in prey distribution associated with temperature stratification in the water column. Our results illustrate the likely complex influences of bathymetry, hydrography and sea ice on the behaviour of male southern elephant seals in a changing environment and highlight the need for region-specific approaches to studying environmental influences on behaviour. Keywords: Southern elephant seals; foraging ecology; satellite-relay data loggers; King George Island; Isla 25 de Mayo; at-sea behaviour.
Keywords: Sørishavet; batymetri; havis; klimaendringer; miljø; næring; seler; sjøis

At-sea behaviour of three krill predators breeding at Bouvetøya—Antarctic fur seals, macaroni penguins and chinstrap penguins - Blanchet, Marie-Anne; Biuw, Martin; Hofmeyr, Greg; de Bruyn, P. J. Nico; Lydersen, Christian; Kovacs, Kit M. (Marine Ecology Progress Series, 2013)
Keywords: Bouvetøya; krill; pelsseler; pingviner; pinnipedier; plankton; seler; zoologi

Changing the Look on Seals from Pole to Pole with Satellite Technology - Blix, Arnoldus Schytte; Folkow, Lars P; Nordøy, Erling S (Adaptation and Evolution in Marine Environments, Volume 2: The Impacts of Global Change on Biodiversity, 2013)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis

Circulation and exchanges at high-latitude ocean margins : dynamical models and observations from instrumented seals - Zhou, Qin; Eltoft, Torbjørn (UiT The Arctic University of Norway, 2013)
Circulation and exchange processes at high-latitude ocean margins are investigated in this thesis, by using analytical models, numerical simulations and hydrographic data. In the Northern Hemisphere, the establishment of Atlantic Water transport as a topographically steered slope current has been investigated. A simplified analytical model based on geostrophic balance predicts that buoyancy loss over a sloping boundary leads to a cross-slope baroclinic flow transformed into an along-slope barotropic flow. And the resulting transport changes can be estimated from hydrographic data. Over the continental slope off Scotland, the diagnosed transport changes in the barotropic flow is in agreement with the observed transport changes. The results emphasize that geostrophy can be used to diagnose topographically steered barotropic flow, which makes it especially useful for high latitudes where topographic steering of ocean circulation is strong. In the Eastern Weddell Sea in the Atlantic Sector of Antarctica, the processes controlling the exchanges of water masses over the continental slope have been studied, by taking advantage of over 11,000 hydrographic profiles collected by instrumented seals in this region from February to November 2008. The proposed mechanism, that the wind-driven downwelling is responsible for the accumulation of Antarctic Surface Water near the ice front and its further spreading beneath the ice shelf along the coast of Eastern Weddell Sea, is revisited by a combination of detailed analysis of the data collected by the seals, an analytical model and numerical simulations. The results show that the Antarctic Surface Water enters the ice shelf cavity after being brought on-shore by wind-driven surface Ekman transport, and being spread below the depth of the ice base within a regime of coastal downwelling. The results also suggest a complex picture of water mass exchange processes along the coast of Eastern Weddell Sea, in which mesoscale eddies play a central role. Finally, the data collected by the seals are employed to evaluate the performance of a global coupled ocean-ice model incorporated with a parametrization of wave-induced mixing in simulating the upper ocean properties in the Southern Ocean. The results suggest that wave-induced mixing is important to modify the upper ocean properties. Since coastal water properties in the Eastern Weddell Sea are mainly determined by the onshore Ekman transport of surface waters, the wave-induced mixing also plays a role in preconditioning the coastal water masses in this region. I dette arbeidet er sirkulasjon og blandingsmekanismer i havområder på høge breddegrader undersøkt ved bruk av analytiske modeller, numeriske simuleringer og havobservasjoner. På den nordlige halvkulen er det undersøkt hvordan transport av Atlanterhavsvann etablerer seg som en topografisk styrt strøm langs kontinentalsokkelskråningen. En forenklet analytisk modell basert på geostrofisk balanse kan forklare hvordan varmetap i vannet som strømmer langs en skrånende bunn fører til en baroklin strøm på tvers av skråningen som igjen blir transformert til en barotrop strøm langs den skrånende bunnen. Denne transportendringen kan man beregne fra hydrografiske data. En slik beregnet transportendring over kontinentalsokkelskråningen vest for Skotland stemmer godt overens med observert transportendring i denne regionen. Resultatene understreker at geostrofi kan bli brukt til å diagnostisere topografisk styrte strømmer, noe som gjør teorien spesielt egnet for å studere oseanografi på høge breddegrader der topografisk styring av strømmene er mest tydelig. I det østlige Weddellhavet, i den atlantiske sektoren av Antarktis, har prosessene som styrer vannmasseutvekslingen på tvers av kontinentalsokkelskråningen blitt undersøkt ved å ta i bruk mer enn 11.000 havprofiler som er blitt samlet inn av seler i denne regionen fra februar til november 2008. Selene var utsyrt med temperatur-, salt- og dybde-loggere. Den foreslåtte mekanismen at vind-drevet nedstrømning er ansvarlig for oppsamling av antarktisk overflatevann nær isbremmen og for dens videre spredning under den flytende isbremmen langs kysten av den østlige Weddellhavet, er testet ved hjelp av en kombinasjon av detaljerte dataanalyser av observasjonene som ble samlet inn av selene, en analytisk modell og numeriske simuleringer. Resultatene viser at det antarktiske overflatevannet entrer hulområdet under isbremmen etter at det er blitt fraktet mot isbremmen som Ekman-transport i overflaten. Spredningen på undersiden av den flytende isbremmen kan forklares ved hjelp av samme mekanisme som nedstrømning langs en kyst. Resultatene tyder også på at vannmasseutvekslingen langs kysten av det østlige Weddellhavet er sammensatt av flere prosesser der virvler av mesoskala størrelse spiller en sentral rolle. Til slutt er dataene som ble samlet inn av selene blitt brukt til å evaluere en global hav-is-modell som har innebygget en parameterisering av bølgedrevet blanding i Sørhavet. Resultatene indikerer at bølgedrevet blanding er viktig for å modifisere hva de øvre vannmassene i Sørhavet er sammensatt av. Siden sammensetningen i kystvann i det østlige Weddellhavet er hovedsakelig bestemt av Ekmantransport inn mot kysten, vil bølgedrevet blanding også spille en rolle når det gjelder å danne kystvannmassene i denne regionen.
Keywords: Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Seler brukt som "forskningsassistenter" for å utforske polhavene - Kovacs, Kit M (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr